Attributable burden of high BMI-related gastrointestinal tract cancers among middle-aged and elderly populations globally, 1990–2021 and projected to 2050: analysis of GBD 2021 - Yilihaer, Yierfan; Tulahong, Alimu; Ruzi, Rexiati; Lin, Yanze; Yuan, Zhongdian; Aikebaier, Ainiwaer; Jiang, Tiemin; Shao, Yingmei; Aji, Tuerganaili (Frontiers in Nutrition, 2026)
BackgroundThe global burden of gastrointestinal tract cancers (GICs)—specifically liver cancer (LC), colorectal cancer (CRC), gallbladder and biliary tract cancers (GBTCs), and pancreatic cancer (PC)—attributable to high body mass index (BMI) is of increasing concern, especially among middle-aged and elderly populations.MethodsUsing data from the Global Burden of Disease (GBD) Study 1990–2021, we assessed deaths, disability-adjusted life years (DALYs), age-standardized mortality rates (ASMR), and estimated annual percentage changes (EAPC) for LC, GBTCs, CRC, and PC attributable to high BMI in middle-aged and elderly populations. We analyzed regional, national, and Socio-demographic Index (SDI)-stratified patterns and their association with SDI and Human Development Index (HDI). Forecasts to 2050 were based on historical trends in these age groups.ResultsFrom 1990 to 2021, LC deaths increased by 363% to 40,958, with ASMR rising from 1.0 to 2.2 per 100,000 (EAPC: 2.4%). GBTC deaths rose by 109% to 19,035, but ASMR slightly declined from 1.1 to 1.0 (EAPC: –0.5%). CRC deaths increased by 140% to 92,013, with stable ASMR (4.9 to 5.0; EAPC: −0.1%). Pancreatic cancer mortality also increased globally (EAPC: 4.4%), with high-SDI regions bearing the highest burden and middle-SDI regions experiencing the fastest growth (EAPC: 18.1%). East Asia bore the highest burden for all cancers, while South Asia showed the fastest mortality increases (EAPC: 5.4% for LC, 2.9% for CRC). At the national level, China and India contributed the largest share of deaths, while Indonesia and Vietnam showed the fastest growth in mortality. High-SDI regions had the largest absolute burden, but middle-SDI regions exhibited the fastest growth. All cancers showed male predominance, peaking at ages 60–79 years (LC: 60–64; GBTCs: 65–69; CRC: 75–79). ASMR followed an inverted U-shaped curve with SDI and HDI, peaking at SDI 0.7–0.9. By 2050, CRC and LC are projected to see rising DALYs and Years Lived with Disability (YLDs) in middle-aged and elderly populations, while GBTCs remain stable, with declining Years of Life Lost (YLLs) rates across all cancers.ConclusionThe escalating burden of high BMI-related GICs—particularly LC, CRC, GBTCs, and PC—in aging populations, especially in developing regions, highlights the urgent need for targeted interventions in prevention, early detection, and survivorship care.